Utilization of QR Code Technology in Population Management and Identification of Cattle in Sindue District, Central Sulawesi - Yudi Mujayin; Hauris Hauris; Fitrah Fakhirah; Alda Pratiwi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The implementation of a QR barcode-based recording system in Sindue District aimed to improve livestock management efficiency. However, digital transformation in rural livestock management faces challenges such as a lack of technological understanding and limited smartphone access. The objective of this study was to analyze livestock farmers' perceptions of the recording system and digital transformation. The method used in this study was a survey with structured interviews (questionnaires) with 66 sample livestock farmers. Data analysis used descriptive statistics and correlation. The results showed that farmers' perceptions of QR barcode technology fell into the